Noise reduction performance of a low energy façade-integrated mechanical ventilator. Issue 2 (June 2021) - Oliveira, Marco A; Bragança, Luis; Silva, Sandra M; Paixão, Dinara; António, Julieta
Acoustic comfort and indoor air quality are essential for the health and wellbeing of the occupants of the building. Thus, the façade must guarantee enough sound insulation and ventilation conditions. However, these aspects conflict because opening windows or using ventilation openings reduces the sound insulation of the envelope and allows the exterior noise entrance. To limit noise transmission into the building, ventilators use passive, active or hybrid noise control techniques. This work addresses the noise reduction performance of a mechanical ventilator for façades, evaluating the effect of different options of passive noise control strategies in the sound insulation of the proposed ventilator. In addition, the air change rate and energy consumption of the ventilator were also investigated. Three prototypes were fabricated and tested at an acoustic chamber, along with ventilation tests carried out in a room equipped with a blower door. CFD simulations were used to enhance the aeraulic geometry of the prototypes, prior to its fabrication. The acoustic experiments showed Dn, e, w values up to 55 dB and noise emission levels lower than 25 dB(A). The use of resistive sound absorbers proved to be more effective in mitigating noise than reactive absorbers, over the entire frequency range. The ventilation tests revealed air change rates of 3.7 h −1 at 50 Pa, while the ventilator's annual energy consumption was 17.52 kWh. The results highlight the proposed device as a viable alternative for decentralised mechanical ventilation, capable of ensuring noise protection and satisfactory ventilation rates, under a sustainable perspective of minimum energy demand.